Team Behaviour and Teamwork - Silaen, Maria (Indonesian Journal of Advanced Research, 2025)
This paper discusses the concepts of team behaviour and teamwork as essential factors in organisational success, particularly within educational institutions. Team behaviour refers to the interaction patterns, communication, and roles among team members, while teamwork represents a synergistic process in which members collaborate to achieve shared goals. The study highlights that effective communication, leadership, trust, task clarity, organisational support, and a conducive environment are critical determinants of team effectiveness. Furthermore, teamwork significantly influences organisational performance by enhancing productivity, innovation, and quality of work. In the educational context, teacher collaboration directly contributes to improving learning outcomes and achieving institutional objectives. The paper also examines challenges such as interpersonal conflicts, lack of trust, unclear roles, leadership issues, and unsupportive organisational culture. To address these, strategies including participatory leadership, team training, trust-building, and the development of a supportive work culture are proposed. Ultimately, the findings underscore the importance of fostering team behaviour and strengthening teamwork to ensure organisational effectiveness and long-term competitiveness.